A Multi-Objective Decision Making Model Based on Goal Programming and Fuzzy AHP Approach for Selecting Investment Projects in Mining Sector - Hadi Mokhtari; Abbas Eftekhari; Mohammad Javadi (مدیریت مهندسی و رایانش نرم)
In mining projects, due to capital constraints and need for high initial investment, prioritizing the investments is one of the most important decisions that should be taken by the managers. Various parameters have effect on this decision which some of them are in conflict with each other. In this study, four parameters have been taken into account as the most important criteria on investment in mining namely initial investment, production cost, profit and staffing . Then, prioritization of investments among the eight mining projects has been modeled. For this purpose, the goal programming method as an efficient multi criteria and objective technique has been used. Owing to  the uncertainty in effect of the parameters and for considering the variety of different decision makers, fuzzy Analytical Hierarchy Process is used to weighting the criteria.